2017
DOI: 10.1007/s10792-017-0596-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visual acuity measurements via three different methods in preschool children: Lea symbols, crowded Lea symbols, Snellen E chart

Abstract: We found SLS, CLS, and SE to be consistent: all three methods can be used to obtain measurements of VA in healthy and amblyopic preschool children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…There are multiple methods of checking visual acuity in children in clinic: Lea symbols, Kay pictures, HOTV, Snellen letter s, Sloan letters, Early Treatment of Diabetic Retinopathy Study (ETDRS), tumbling “E”; all with and without crowding bars. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 Lea symbols, HOTV, and letter acuity have been recommended for use in children. 8 , 11 Visual Acuity is also mass-tested in vision screening programs with the goal of detecting children with visual impairment as recommended by the American Academy of Pediatrics and the American Association for Pediatric Ophthalmology and Strabismus.…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple methods of checking visual acuity in children in clinic: Lea symbols, Kay pictures, HOTV, Snellen letter s, Sloan letters, Early Treatment of Diabetic Retinopathy Study (ETDRS), tumbling “E”; all with and without crowding bars. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 Lea symbols, HOTV, and letter acuity have been recommended for use in children. 8 , 11 Visual Acuity is also mass-tested in vision screening programs with the goal of detecting children with visual impairment as recommended by the American Academy of Pediatrics and the American Association for Pediatric Ophthalmology and Strabismus.…”
Section: Introductionmentioning
confidence: 99%
“…A lower percentage of failure in the older group, 48-59 months, can be attributed to the visual maturation process. 2 Almost every other study also found that preschool children tended to be more cooperative with Lea symbols. 1,11,14 However, a 2017 study found a 5-11% better testability rate with Tumbling E in children aged 3-4 years compared to previous studies which was hypothetically connected with stimulation of spatial orientation through a smartphone.…”
Section: Resultsmentioning
confidence: 95%
“…There are two types of charts, either using letter optotypes, such as in HOTV, Landolt C, and Tumbling E (E-chart), or using picture optotypes, as in Lea symbols. 2 The Lea symbols chart was the first logMAR-based chart that was well-accepted for pediatric visual acuity tests. It consists of three symbols (apple, square, and house) which have several crucial differing features from the fourth symbol, a circle.…”
mentioning
confidence: 99%
“…It was designed to avoid some cultural barriers using common pictures (square, circle, house, heart), and speech problems or shyness with the option of matching gures [5,15]. Many studies have compared LEA symbols and letter optotypes in children, most of them showing good agreement [16][17][18]. However, the question about comparison between symbols and letters is still open, because some works addressed a tendency to higher VA values when measuring with LEA [19][20], while others turn to perform on the contrary [21].…”
Section: Resultsmentioning
confidence: 99%